Benefits and adverse effects associated with yoga practice: A cross-sectional survey from India - Shirley Telles; Sachin Kumar Sharma; Dipak Chetry; Acharya Balkrishna (Elsevier, 2021)
Objective: Benefits and adverse effects of yoga were reported in surveys from different countries. The present study aimed to (i) determine the benefits and adverse effects of yoga in yoga experienced persons in India and (ii) correlate these effects of yoga with factors related to the individual and their yoga practice. Design and setting: This convenience sampling in-person survey reports benefits and adverse effects of yoga in 3135 yoga experienced persons. Results: The benefits of yoga were reported by 94.5 percent of the respondents. The three most common benefits were improvement in: (i) physical fitness, (ii) mental state and (iii) cognitive functions. An adverse effect of yoga was reported by 1.9 percent of the respondents. The three most common adverse effects reported were: (i) soreness and pain, (ii) muscle injuries and (iii) fatigue. The following factors showed a significant association (in all cases p < 0.05 Chi square test; Cramer's V > 0.10) with reported benefits of yoga: (i) experience of yoga in months, (ii) time spent practicing yoga in a week, (iii) number of yoga techniques practiced, and (iv) whether awareness was maintained during the yoga practice or not. Conclusion: Benefits of yoga practice to physical health were the most common, with soreness and pain the most common adverse effect of yoga. Yoga practice related factors influence the benefits of yoga.